Real-world data confirming the efficacy and safety of decitabine in acute myeloid leukaemia – results from a retrospective Belgian registry study. Issue 2 (4th March 2021) - Meers, Stef; Bailly, Benjamin; Vande Broek, Isabelle; Malfait, Bart; Van Hoorenbeeck, Sandra; Geers, Janice; Braakman, Joost; Van Kouwenhove, Marieke; Doyle, Margaret; Diels, Joris; Caekelbergh, Karin; Chevalier, Pierre; et al.
ABSTRACT: Objectives : Currently, there is no standard treatment for patients with acute myeloid leukaemia (AML) ineligible for standard induction chemotherapy (IC). This study aimed to report real-world evidence data on the efficacy and safety of decitabine in this patient group. Methods : This study was a Belgian, retrospective, non-interventional, multicentre registry of patients ≥ 65 years, with newly-diagnosed de novo or secondary AML ineligible for IC. Patients were treated according to routine clinical practice. Overall survival (OS), progression-free survival (PFS) and transfusion independence for ≥8 consecutive weeks were evaluated. Results : Forty-five patients were enrolled, including 67% (n = 30) with secondary AML. Median OS and PFS were 7.3 months (95% CI: 2.2–11.1) and 4.1 months (95% CI: 2.1–7.6) respectively. A subpopulation analysis showed that patients treated with ≥4 cycles (n = 21) had significantly better outcomes compared to patients receiving <4 cycles (median OS 17.5 vs 1.6 months; median PFS 17.5 vs. 1.4 months). Twenty-five percent and 58% of patients that were respectively RBC or platelet transfusion-dependent at baseline became transfusion independent during treatment. Conclusion : This real-world data confirms that decitabine can lead to transfusion independence and longer OS in AML patients, particularly after administering ≥4 cycles, as indicated in the summary of product characteristics.